Case Report: Successful endovascular treatment of acute type A aortic dissection - Pitts, Leonard; Heck, Roland; Montagner, Matteo; Penkalla, Adam; Kofler, Markus; Falk, Volkmar; Kempfert, Jörg; Buz, Semih (Frontiers in Cardiovascular Medicine, 2023)
Open surgical repair remains the current gold-standard for treatment of acute type A aortic dissection. However, especially elderly patients with relevant comorbidities who are deemed unfit for open surgery may benefit of a minimally invasive endovascular approach.Methods: We report a case of an 80 year old male patient with retrograde acute type A aortic dissection and peripheral malperfusion after receiving thoracic endovascular aortic repair due to thoracic aortic aneurysm. Our individualized endovascular approach consisted of left carotidsubclavian bypass, proximal extension of thoracic endovascular aortic repair using a covered stent graft and a single covered stent graft for the ascending aorta in combination with an uncovered stent for the aortic arch.Postoperative computed tomography angiography demonstrated excellent outcome with no signs of endoleak or patent false lumen. Follow-up after 3.5 years showed a stable result with no signs of stent failure or dissection progress. No aortic re-interventions were needed in the further course.Discussion: An individualized endovascular approach may be justified for acute type A aortic dissection in elderly patients with high surgical risk if performed in specialized aortic centers.